PENGARUH UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP TAX AVOIDANCE DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Wisnu Bagus Wicaksono; Heppy Purbasari (JURNAL ILMIAH EDUNOMIKA, 2025)
Tax avoidance is a legal strategy carried out by companies to reduce tax payments by making maximum use of applicable tax rules. However, tax avoidance isconsidered illegal if the transaction is carried out only with the aim of avoiding tax obligations. Therefore, even though it is small-scale, tax avoidance practices can have a negative impact on Indonesia as a whole. Tax avoidance can be influenced by various factors, namely company size, sales growth, and audit committee as moderation variables. The purpose of this study to exploit tax avoidance in terms of company size, sales growth, and audit committee in reducing tax avoidance. The sample of this study is LQ45 companies listed on the Indonesia Stock Exchange (IDX) during the 2021 2022 period. The sampling method uses the purposive sampling method and the number of samples in this study is 85 companies. The result of this study is that sales growth has a significant effect on tax avoidance, while company size has no effect on tax avoidance, the audit committee is unable to moderate the influence of company size and sales growth Against Tax Avoidance.